A CLINICAL STUDY TO EVALUATE THE EFFICACY OF SAMANGADI ROPANA TAILA IN THE MANAGEMENT OF DUSHTA VRANA (CHRONIC ULCERS) - Poonam, *Mohod; Sudesh, Gupta; Kirandeep, Kour; Sharad, Mohod (International Journal of Ayurveda and Pharma Research, 2015)
Chronic ulcers are the problems and challenges for doctors in day today practice. An ulcer is the one of the type of wound which breaks integrity or continuity of skin or mucous membrane. Many studies have been carried out in Ayurveda for the management of chronic ulcers. Shashti Upakrama i.e. sixty types of wound management are the best therapies to deal for chronic ulcers. In the light of Ayurvedic knowledge, Sushruta described Samangadi Ropana taila as topical application in the context of Vrana. It contains Manjishta, Haridra, Padma, Triphala, Tuth, Vidanga, Kutki, Haritaki, Guduchi and Karanja. These drugs have Vrana Shodhana (wound cleaning) and Vrana Ropana (wound healing) properties. The present study was carried out on all types of Dushta Vrana (chronic ulcer). The Taila was applied topically once daily for 30 days or till healing of wound whichever is earlier. In this study 30 patients were selected and the study was single blind clinical study to evaluate the efficacy of Taila by the subjective and objective criteria. This study shown that, there were significant results found in Dushta vrana (chronic ulcer) by anti-infective (anti bacterial, anti-fungal and anti-parasitic) property. It also contains analgesic and anti-inflammatory property which reduces pain, discharge, inflammation, tenderness, burning sensation and itching which contribute healthy granulation tissue formation. Thus wound healing restored without producing any adverse effect.